2019
DOI: 10.1038/s41467-019-10979-3
|View full text |Cite
|
Sign up to set email alerts
|

Small extracellular vesicles containing arginase-1 suppress T-cell responses and promote tumor growth in ovarian carcinoma

Abstract: Tumor-driven immune suppression is a major barrier to successful immunotherapy in ovarian carcinomas (OvCa). Among various mechanisms responsible for immune suppression, arginase-1 (ARG1)-carrying small extracellular vesicles (EVs) emerge as important contributors to tumor growth and tumor escape from the host immune system. Here, we report that small EVs found in the ascites and plasma of OvCa patients contain ARG1. EVs suppress proliferation of CD4 + and CD8 + T-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
180
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 226 publications
(181 citation statements)
references
References 63 publications
1
180
0
Order By: Relevance
“…Further studies by Liu and colleagues reported that also mice glioblastoma cells-EVs promote in vivo tumor cell growth by inhibiting CD8+T cell cytolytic activity [57]. In more recent studies, Maybruck and colleagues correlated the EV-mediated dysfunction of CD8+T cells, in head and neck cancer, with the presence of the immunoregulatory protein, galectin-1 [58], while in ovarian carcinoma, tumor EVs inhibit the proliferation of CD4+ and CD8+ T cells by delivering the metabolic checkpoint molecule arginase-1 [59]. One of the major mechanisms by which tumor cells can inhibit CD8+ T cell functions is correlated with activation of immune checkpoints as that mediated by the PD-1/PD-L1 pathway.…”
Section: Tevs and T Lymphocyte Cellsmentioning
confidence: 99%
“…Further studies by Liu and colleagues reported that also mice glioblastoma cells-EVs promote in vivo tumor cell growth by inhibiting CD8+T cell cytolytic activity [57]. In more recent studies, Maybruck and colleagues correlated the EV-mediated dysfunction of CD8+T cells, in head and neck cancer, with the presence of the immunoregulatory protein, galectin-1 [58], while in ovarian carcinoma, tumor EVs inhibit the proliferation of CD4+ and CD8+ T cells by delivering the metabolic checkpoint molecule arginase-1 [59]. One of the major mechanisms by which tumor cells can inhibit CD8+ T cell functions is correlated with activation of immune checkpoints as that mediated by the PD-1/PD-L1 pathway.…”
Section: Tevs and T Lymphocyte Cellsmentioning
confidence: 99%
“…Another role of ascites-derived exosomes is to serve as the immunosuppressor. Arginase-1 (ARG1)-carrying exosomes accelerate ovarian cancer growth by suppressing T-cells Phosphatidylserine in ascites inhibits T-cell activity and Fas ligand induces the apoptosis of T-cells [41][42][43] Labani-Motlagh et al reported that phosphatidylserine, natural-killer receptor group 2, member D (NKG2D) and DNX accessory molecule-1 (DNAM-1) ligands in ascites-derived exosomes inhibited NK cell activity, resulting in immune suppression [40]. As described above, exosomes contribute to multiple steps during invasive processes and to early steps in peritoneal dissemination and metastasis.…”
Section: Roles Of Exosomes During Ovarian Cancer Progressionmentioning
confidence: 99%
“…Thereafter, CAF-derived exosomes promote epithelial-mesenchymal transition to ovarian cancer cells[48,49]. (4) Ovarian cancer cell-derived exosomes inhibit immune cells and facilitates the conversion of macrophages to tumor-associated macrophages[38,[40][41][42]44,45]. (B) The involvement of exosomes in peritoneal dissemination (5).…”
mentioning
confidence: 99%
“…Indeed, the ability of many soluble protein-dependent mechanisms to alter distant DC function such as in draining lymph node tissues is more limited. The recent realization that tumor-derived exosomes are capable of genetically altering distant immune cell populations implies that these extracellular vesicles and their molecular cargo are likely to be very important players in DC tolerization and tumor-mediated immune evasion (54,55,77).…”
Section: Wnt Ligandsmentioning
confidence: 99%